2020
DOI: 10.1242/jcs.238816
|View full text |Cite
|
Sign up to set email alerts
|

Capacitation-associated alkalization in human sperm is differentially controlled at the subcellular level

Abstract: Capacitation in mammalian sperm involves the accurate balance of intracellular pH (pH i), but the mechanisms controlling this process are not fully understood, particularly regarding the spatiotemporal regulation of the proteins involved in pH i modulation. Here, we employed an image-based flow cytometry technique combined with pharmacological approaches to study pH i dynamics at the subcellular level during capacitation. We found that, upon capacitation induction, sperm cells undergo intracellular alkalizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 80 publications
1
38
0
1
Order By: Relevance
“…Our results are consistent with others’ observations that the sAC and PKA pathways are important in regulating sperm capacitation in many species and that these pathways act, at least in part, by regulating pH i ( Puga Molina et al, 2017 ; Chavez et al, 2019 ; Matamoros-Volante and Trevino, 2020 ; Balbach et al, 2021 ). Carlson et al showed no changes in pH i induced by HCO 3 – in mouse sperm.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with others’ observations that the sAC and PKA pathways are important in regulating sperm capacitation in many species and that these pathways act, at least in part, by regulating pH i ( Puga Molina et al, 2017 ; Chavez et al, 2019 ; Matamoros-Volante and Trevino, 2020 ; Balbach et al, 2021 ). Carlson et al showed no changes in pH i induced by HCO 3 – in mouse sperm.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have revealed that HCO 3 – raises sperm intracellular pH (pH i ) ( Demarco et al, 2003 ; Chavez et al, 2019 ; Matamoros-Volante and Trevino, 2020 ) and that HCO 3 – can activate CatSper channels in mouse sperm ( Orta et al, 2018 ). Therefore, we investigated whether the [Ca 2+ ] i changes induced by HCO 3 – were due to a change in pH i .…”
Section: Resultsmentioning
confidence: 99%
“…The information on the role of chloride channels (and transporters) in spermatozoa is rather scarce when compared to other ion channels. Nevertheless, in sperm cells, they seem to support events such as the hyperpolarization of the plasma membrane [82], the alkalization of cytosolic environments [83,84] and cAMP/PKA-induced protein phosphorylation [84]. All of these processes are typical features of sperm capacitation.…”
Section: Chloride Channelsmentioning
confidence: 99%
“…Sperm capacitation is characterized by a set of physiological changes preparing the male gamete for fertilization [1]. These physiological changes include increased beat frequency and curvilinear motility, intracellular pH (pH i ) alkalinization, rise in intracellular calcium levels, augmented membrane lipid disorder and tyrosine phosphorylation of specific proteins, which are required for sperm to trigger acrosomal exocytosis [1][2][3][4][5][6][7][8]. Several channels are implicated in the increase of pH i during capacitation and acrosomal reaction in mammalian spermatozoa, including HCO 3 − membrane transporters, Na + -H + exchangers (NHEs), monocarboxylate transporters (MCTs) and voltage-gated proton channels (HVCN1) [9,10].…”
Section: Introductionmentioning
confidence: 99%